Effect of dust size and structure on scattered-light images of protoplanetary discs. Issue 4 (8th March 2019) - Tazaki, Ryo; Tanaka, H; Muto, T; Kataoka, A; Okuzumi, S
Abstract: We study scattered-light properties of protoplanetary discs at near-infrared wavelengths for various dust size and structure by performing radiative transfer simulations. We show that different dust structures might be probed by measuring disc polarization fraction as long as the dust radius is larger than the wavelength. When the radius is larger than observing wavelength, disc scattered light will be highly polarized for highly porous dust aggregates, whereas more compact dust structure tends to show low polarization fraction. Next, roles of monomer radius and fractal dimension for scattered-light colours are studied. We find that, outside the Rayleigh regime, as fractal dimension or monomer radius increases, colours of the effective albedo at near-infrared wavelengths vary from blue to red. Our results imply that discs showing grey or slightly blue colours and high polarization fraction in near-infrared wavelengths might be explained by the presence of large porous aggregates containing sub-micron-sized monomers.